Corporate governance, product market competition and debt financing - Teodora Paligorova; Jun Yang (Bank of Canada, 2014)
This paper examines the impact of product market competition and corporate governance on the cost of debt financing and the use of bond covenants. We find that more antitakeover provisions are associated with a lower cost of debt only in competitive industries. Because they are exposed to higher takeover risk in competitive industries, bondholders charge higher bond spreads to firms that have fewer anti-takeover provisions. Once firms' anti-takeover provisions are in place, we find that bondholders use fewer payment and debt priority covenants in competitive industries. Our results suggest that product market competition plays a crucial role in explaining the way a firm's anti-takeover protection affects the cost of debt and the use of bond covenants.
Keywords: G12; G34; 330; Financial markets